Percepções sobre risco e efeitos do uso e consumo de esteroides anabolizantes por praticantes de musculação - Guilherme G. Bevilacqua; Ricardo Brandt; Guilherme T. Vilarino; Vitor da S. Borges; Maick da S. Viana; Bianca C. Dezordi; Luiz F. do Amaral Filho; Alexandro Andrade (Universidade Estadual do Oeste do Paraná, 2016)
It is known that the design of the harm caused by the indiscriminate use of anabolic steroids is short of the potential harm that misuse can cause. Were investigated 50 men users of anabolic androgenic steroids (AAS). All participants are bodybuilders, mean age 29 years (±7). Most have completed higher education (n=12; 26.1%) or are enrolled in higher education (n=17; 37%). The highest form of knowledge to AAS was for gym colleagues (n=10; 20%) and 17 (34%) show more than one. Twenty-nine (58%) received parenteral AAS, 46.5% (n=20) self-made application and the most frequently EAA cited were Durateston (n= 39; 78%) and Deca-Durabolin (n=38; 76%). Twenty six (59.1%) surveyed said they had used AAS for veterinary use. For 64% (n=32) of the participants have a physical thinner was the main justification for the use of AAS; the positive effect most noticeable was the improvement of athletic performance. Thus it appears that individuals who use AAS have, to share the risks of misuse, and that prevention campaigns should go beyond to warn of the harmful effects of AAS use.